Current scenario of dwarf threadworm, Strongyloides stercoralis infections in Southern Rajasthan, a systemic review - Bhumbla, Upasana; Kothari, Aditi; Rao, Jatin; Dalal, A.S. (Tropical Journal of Pathology and Microbiology, 2020)
Strongyloides stercoralis is an intestinal nematode in humans. It is estimated that tens of millions people are infected worldwide, although no precise estimate is available. Although most infected individuals are asymptomatic, S. stercoralis is capable of transforming into a fulminant fatal illness under certain conditions associated with a compromise of host immunity. Strongyloides stercoralis has a complex biology with two separate life cycles, the freeliving cycle and the parasitic cycle. Filariform larvae in the soil infect the human host by penetration of intact skin to begin the parasitic cycle.